2016
DOI: 10.1002/chem.201602543
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Hydrogen Bonding Modulates Electronic Properties and Controls Self‐Assembly of Donor/Acceptor Semiconductors

Abstract: A comprehensive investigation of the complementary H-bonding-mediated self-assembly between dipyrrolo[2,3-b:3',2'-e]pyridine (P2P) electron donors and naphthalenediimide/perylenediimide (NDI/PDI) acceptors is reported. The synthesis of parent P2P and several aryl-substituted derivatives is described, along with their optical, redox, and single-crystal packing characteristics. The dual functionality of heteroatoms in the P2P/NDI(PDI) assembly, which act as proton donors/acceptors and also contribute to π-conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…On the contrary, the orbital‐interaction effect (ii) causes a reverse negative‐charge transfer from the donor ( IC ) to the acceptor (quinone), which is more significant for stronger acceptors, hence explaining the trend of diminishing HLG decrease. Smaller changes (0.1 to 0.3 eV) in the orbital energies have been previously predicted for nucleobases and some D/A complexes . However, to the best of our knowledge, such a drastic perturbation of the HLG modulated by hydrogen bonding is unprecedented in π‐functional D/A systems.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…On the contrary, the orbital‐interaction effect (ii) causes a reverse negative‐charge transfer from the donor ( IC ) to the acceptor (quinone), which is more significant for stronger acceptors, hence explaining the trend of diminishing HLG decrease. Smaller changes (0.1 to 0.3 eV) in the orbital energies have been previously predicted for nucleobases and some D/A complexes . However, to the best of our knowledge, such a drastic perturbation of the HLG modulated by hydrogen bonding is unprecedented in π‐functional D/A systems.…”
Section: Resultsmentioning
confidence: 57%
“…Previously, we explored weak‐CT co‐assemblies of dipyrrolopyridine (P2P) donors and naphthalenediimide (NDI) acceptors mediated by complementary DAD/ADA H‐bonding and showed their functionality as dual( p / n )‐channel semiconductors in OFETs . Density‐functional‐theory (DFT) calculations suggested that H‐bonding leads to a small but consistent reduction of the HOMO–LUMO offset by 0.11–0.19 eV . We explained this perturbation by the partial dislocation of two protons from P2P to NDI, which results in a negative polarization on the P2P donor and a positive polarization on the NDI acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…This was expected and confirms the loss of the tBOC group and transformation of 4 to 3. [22][23][24][25] These results show that the thermal deprotection strategy is effective at generating 3 in situ, and that 3 forms very stable thin films on glass (i.e.…”
Section: Thermal Propertiesmentioning
confidence: 77%
“…Such differences are due to extent of charge‐transfer between the acid and L, which is guided by the complementary hydrogen bonds. Such effect plays major role to tune optical properties . The observed colour differences have alerted us to explore stacking interactions of ‐ nap‐acid ‐ in these adducts.…”
Section: Resultsmentioning
confidence: 99%